(untitled) (Physical Education, Health and Social Sciences, 2025)
Professional development (PD) of university teachers is widely recognized as a critical mechanism for enhancing teaching quality, strengthening research capacity, and improving student learning outcomes in higher education. In Pakistan, particularly in the province of Khyber Pakhtunkhwa (KP), universities have increasingly invested in faculty development initiatives; however, systematic evidence regarding the design, effectiveness, and impact of these programs remains fragmented and underexplored. This study presents a systematized review of empirical and grey literature to examine the key features of professional development programs for university teachers in KP, identify the factors influencing their effectiveness, and assess their impact on teaching practices, research competence, and student learning outcomes. A structured and transparent search strategy was employed across multiple international and national databases, including Scopus, Google Scholar and local university repositories. Studies published between 2000 and 2025 were screened using predefined inclusion and exclusion criteria. The selected literature was analyzed through thematic synthesis to identify recurring patterns, contextual factors, and outcome trends. The findings reveal that professional development programs in KP predominantly focus on pedagogical skills, research capacity building, instructional technology, and academic leadership, with delivery formats ranging from short-term workshops to sustained mentoring and blended learning models. Program effectiveness is strongly influenced by individual faculty motivation, relevance and coherence of program content, quality of facilitation, institutional leadership support, and availability of resources. Evidence across the reviewed studies indicates that well-structured and contextually aligned PD initiatives contribute to improved teaching practices, increased research productivity, enhanced scholarly confidence, and positive student engagement and learning outcomes.